IDDF2022-ABS-0190 Prevalence and outcomes of acute-on-chronic liver failure in australia – a single-centre study. (2nd September 2022) - Chetwood, John; Sabih, Abdul-Hamid; Chan, Karen; Salimi, Shirin; Sheiban, Alex; Lin, Elton; Chin, Simone; Gu, Bonita; Sastry, Vinay; Tsoutsman, Tatiana; Bowen, David; Majumdar, Avik; et al.
Abstract : Background: Acute-on-chronic liver failure (ACLF) is a distinct entity to acute decompensation (AD) of cirrhosis. There is no published Australian data regarding the epidemiology and outcomes of ACLF. Methods: We performed a retrospective cohort study of adults with cirrhosis admitted with a decompensating event at a quaternary referral liver transplantation (LT) centre 2015–2020. ACLF was defined using the European Association for the Study of the Liver-Chronic Liver Failure (EASL-CLIF) definition, those who did not meet the definition were classified as AD. ACLF was graded according to a number of organ failures. The primary outcome of interest was 90-day LT-free survival. Results: During the study period, 615 patients had 1039 admissions for a decompensating event. On their index admission, 34% (209/615) of patients were classified as ACLF. The principal admission issues with ACLF were: encephalopathy (34%, 71/209), ascites (30%, 62/209), & infection (22%, 45/209). Compared to AD, ACLF patients were similar in sex (68% vs 66% male, p=0.58), age (median 57 vs 57 years, p=0.66), & had no difference in cirrhosis aetiologies. The median admission Model for End-stage Liver Disease (MELD) & MELD-Na scores were higher in the ACLF cohort (21 vs 17, 25 vs 20 respectively, both p<0.001). In the ACLF cohort (per index admission), ACLF was Grade 3 (50%), Grade 2 (30%) & Grade 1 (21%). At 90-days follow-up, there were 71/209 (34%) deaths & 71/209 (34%) LT in the ACLF cohort vs 51/406 (13%) & 41/406 (10%) LT in the AD cohort. Both the presence & severity of ACLF grade >1 significantly predicted for worse LT-free survival compared to patients with AD (IDDF2022-ABS-0190 Figure 1, IDDF2022-ABS-0190 Figure 2). The European foundation for the study of chronic liver failure ACLF score (CLIF-C ACLF), MELD & MELD-Na scores performed similarly in predicting 90-day mortality or LT: area under the receiver operating characteristic curve were 0.77 vs 0.80 vs 0.80, respectively, p>0.05. Conclusions: ACLF grade 2–3 complicates >25% of hospital admissions for cirrhosis with decompensating events & is associated with high short-term mortality without LT.